Effects of low energy availability on performance in male athletes: a scoping review - Hänisch, T.; Niess, A.; Carlsohn, A. (Journal of Science and Medicine in Sport, 2024)
Objectives The primary aim of this study was to investigate the effects of low energy availability (LEA) on different performance outcomes in male athletes. Secondary aims were to examine an assumed dose-response relationship and identify knowledge gaps.